2010
DOI: 10.1002/ange.200906023
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Small Carbon Nanotube: The Surprising Appearance of D5h(1)‐C90

Abstract: Vollkommen röhrenförmig: Das bislang nicht nachgewiesene höhere Fulleren D5h(1)‐C90 (siehe Struktur) wurde als Haupt‐C90‐Isomer isoliert, wenn von Sm2O3‐dotierten Graphitstäbchen ausgegangen wurde, und durch eine Röntgenstrukturanalyse charakterisiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
64
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 28 publications
10
64
0
3
Order By: Relevance
“…Interestingly, nanotubular fullerenes (i. e. D 5h (1)-C 90 , [13] D 3d (3)-C 96 , La 2 @D 5 A C H T U N G T R E N N U N G (450)-C 100 , [14] and Sm 2 @D 3d A C H T U N G T R E N N U N G (822)-C 104 . [15] ) occur for each of the largest cages that have been fully structurally characterized.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Interestingly, nanotubular fullerenes (i. e. D 5h (1)-C 90 , [13] D 3d (3)-C 96 , La 2 @D 5 A C H T U N G T R E N N U N G (450)-C 100 , [14] and Sm 2 @D 3d A C H T U N G T R E N N U N G (822)-C 104 . [15] ) occur for each of the largest cages that have been fully structurally characterized.…”
mentioning
confidence: 98%
“…[16,17] Experimentally, Kikuchi, Achiba and co-workers briefly reported that they had isolated ten isomers of C 96 and identified their symmetries through 13 C NMR spectroscopy as C 1 (4 isomers), C 2 (3 isomers), C s (l isomer), D 2 (1 isomer), and D 3d (l isomer). [18] Kemnitz and Troyanov reacted C 2 F 5 I with a mixture of higher fullerenes and were able to obtain crystals of the adduct C 96 A C H T U N G T R E N N U N G (C 2 F 5 ) 12 , which were shown by singlecrystal X-ray diffraction to utilize the C 1 A C H T U N G T R E N N U N G (145)-C 96 cage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of C90, we choose its D5h isomer in virtue of its higher symmetry; we also note that this is the most abundant C90 isomer occurring in soot generated from Sm2O3-doped graphite rods. [26] To begin with (Table 1), C60 and C70 are independently considered inside all of the seven accessible capsule conformers (four homochiral, three meso, as explained earlier). However, for C76, C78, C84, and C90 complexes, investigation is subsequently limited to the five 12 conformers that are shown in Table 1 to yield the most favorable encapsulation energies with C70.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…However, most recently a fullerene C 90 have been successfully isolated and characterized [11][12]. The obtained C 90 fullerene exhibits D 5h symmetry and a tubular shape according to the X-ray crystallographic study [12].…”
Section: Introductionmentioning
confidence: 99%